KEBIJAKAN PEMERINTAH INDONESIA DALAM MENGANTISIPASI PERKEMBANGAN GERAKAN TERORISME DI KAWASAN ASIA TENGGARA TAHUN 2010-2015 - Winda Astari; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describe the policy of Indonesias Government in anticipation growth of terorism activity in Southeast Asia Region in 2010-2015. Southeast Asia are one of regions are have increase of terorism activity. Its have been proved by teror activity in Indonesia, Malaysia and Singapore by Jamaah islamiyah and Abu Sayyaf Group in Filipina. Toward that Indonesia Governmnet has been create some policy to anticipated that threats.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the policy of Indonesias Government in anticipation growth of terorism activity in Southeast Asia Region. The theories applied in this research are realisme perspective with transnational crime concept.The result shows that the policy of Indonesias Government in anticipation growth of terorism activity in Southeast Asia Regions are with the national policy by preventive, pre emptive and represive actions. In international policy Indonesia have create some policy with Indonesia active in Asean Region Forum, Indonesia dealed about Asean convention on againt terorism and ASEANAPOL conference and Indonesia also have been agreement with United States America and European Union to anticipate the terorism activity in Southeast Asia Regions.Key words: policy, threats, terorism and ASEAN